Cognitive styles and loudness discrimination: individual differential analysis - Natalia N. Volkova; Aleksey N. Gusev (Национальный психологический журнал, 2018)
Background. The paper highlights the necessity of studying the role of various high-level psychological mechanisms that participate in regulating sensory perceptual processes occurring under perceptual uncertainty. Objective. The objective was to study the role of cognitive styles as crucial factors of individual differences that determine the performance of near-threshold and threshold sensory tasks on loudness discrimination. Design The tasks represented the discrimination of loudness of 1000Hz tonal signals in the ‘similar-different’ paradigm. The stimulus factor was presented by the difficulty level set by the value of difference between the stimuli (2 or 1 dB). Five cognitive styles (augmenting-reducing, leveling-sharpening, flexibility-rigidity of cognitive control, equivalence range, and focusing-scanning) were considered as factors of individual differences. The sensitivity index A`, RT and its stability, and also confidence index for each task were analyzed. Results. The significant and quasi-significant (0.05<p<0.1) effects of separate cognitive styles and also their interactions effects were identified. These effects varied depending on the task difficulty level. Cognitive styles ‘augmenting-reducing’ (p=0.008) and ‘leveling-sharpening’ (p=0.044), together with their interaction (p=0.042), affected sensitivity in threshold task; the interaction of these styles affected sensitivity in near-threshold task (p=0.047). ‘Flexibility-rigidity of cognitive control’ (p=0.042) as well as the interaction of ‘augmenting-reducing’ and ‘leveling-sharpening’ affected RT (p=0.073) and its stability (p=0.083). Subjective confidence in the near-threshold task depended on such cognitive styles as ‘flexibility-rigidity of cognitive control’ (p=0.081), and ‘equivalence range’ (p=0.043); the threshold task depended on ‘focusingscanning’ (p=0.021), ‘flexibility-rigidity of cognitive control’ (p=0.071), and ‘equivalence range’ (p=0.018), alongside the interaction of the latter two (p=0.052). The results were compared to the ones of threshold and near-threshold visual signal detection tasks performance. Conclusion. Being crucial situational determinants of solving sensory tasks under perceptual uncertainty, the type and difficulty level of the task mediate the effects of individual differences factors on sensory performance indices. The results are discussed within the framework of system activity approach in psychophysics.